2018
DOI: 10.3233/cbm-171120
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-29a suppresses cell proliferation by targeting SIRT1 in hepatocellular carcinoma

Abstract: Thus, these results indicated that miR-29a may serve as a potential target of HCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…In fact, miR-29a and miR-29c are members of the miR-29 family, which is known to be associated with tumorigenesis and cancer progression [29]. MiR-29a might act as either an oncogene or tumor suppressor in a wide variety of malignancies [30]. Besides, numerous studies [4,5] have identified the significant upregulation of miR-29a in serum and plasma from CRC patients compared to controls, as we have demonstrated in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, miR-29a and miR-29c are members of the miR-29 family, which is known to be associated with tumorigenesis and cancer progression [29]. MiR-29a might act as either an oncogene or tumor suppressor in a wide variety of malignancies [30]. Besides, numerous studies [4,5] have identified the significant upregulation of miR-29a in serum and plasma from CRC patients compared to controls, as we have demonstrated in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have shown that miR-29a played an important role in HCC cells [8,9]. MiR-29a could reduce the proliferation of HCC cells by targeting silent mating type information regulation 2 homolog-1 (SIRT1) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that miR-29a played an important role in HCC cells [8,9]. MiR-29a could reduce the proliferation of HCC cells by targeting silent mating type information regulation 2 homolog-1 (SIRT1) [8]. MiR-29a inhibited the expression of recombinant claudin 1 (CLDN1) to reduce the migration and proliferation of HCC cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are differently expressed in a number of types of human cancer, including HCC (11), and ovarian (12), thyroid (13) and gastric cancer (14). Dysregulated miRNAs serve a pivotal role in numerous biological behaviors, including cell proliferation, cell cycle, apoptosis, metastasis and angiogenesis (15)(16)(17). miRNAs are able to serve tumor-suppressing or oncogenic roles in the formation and progression of HCC, which primarily depends on the characteristic of their target genes (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are able to serve tumor-suppressing or oncogenic roles in the formation and progression of HCC, which primarily depends on the characteristic of their target genes (18,19). For example, miR-29a inhibits HCC cell proliferation, colony formation and inhibits cell cycle progression by directly targeting Sirtuin 1 (15). miR-1468 is upregulated in HCC and promotes aggressive tumor behaviors by activating peroxisome proliferator-activated receptor gamma-mediated protein B kinase signaling (20).…”
Section: Introductionmentioning
confidence: 99%